أثر التغيرات الإنتاجية في ظل البيئة الالكترونية على الانظمة الكلفوية - د. صالح ابراهيم يونس الشعباني (PROSPECTIVE RESEARCHES, 2023)
In the last few years , there appeared in the industrial field modern productive systems that are electronically operated such as the JIT (Just In Time) system and the CIM(Computer Integrated Manufacturing),Along with these systems,there was high automation and change in the working out of the productive operation This changes in the industrial environment has influenced the classical systems since they have not been able to cope with these changes . This has resulted in a negative influence on the determination of product s cost and the degree of the suitability of costing information and the rapidity in presenting it. As a result, there was a search for new cost systems so that they would be able to cope with the industrial changes . Hybrid systems, therefore, have appeared, viz. backflush cost system and Activity-based cost system .The applications of these systems had effects on the cost accounting policies and procedures as well as on the cost management strategy. This research sheds light on the changes in the manufacturing environment and the needs for new cost system. It ends with a clarification of the concept, philosophy and the application of these systems and their effects on the accounting procedures.